Risālah al-Bīrūnī fī Fihrist Kutub al-Rāzī: a comprehensive bibliography of the works of Abū Bakr al-Rāzī (D.313 A.H/925) and al-Bīrūnī (D.443/1051) - Deuraseh, Nurdeng @ Nurdeen (Department of 'Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya, 2008)
Risālah al-Bīrūnī fī Fihrist Kutub al-Rāzī is a bibliographical document of two Muslim scholars namely Abū Bakr Muḥammad ibn Zakariyā al-Rāzī (m. 313/925) and Abū al-Rayḥān Muḥammad ibn Aḥmad al-Bīrūnī (m. 443/1051). It is a comprehensive bibliography compared with what had been made by Ibn Nadīm (m.384/ 995), Ibn Juljul (d. 385/996 C.E), al-Bayhaqī (d. 565 A.H/1170), al-Qifṭī (d.645/1248), Ibn Abī Uṣaybi‘ah (d.668 /1266) and Ibn Khallikān (d.681/1283 C.E). The Risālah was written in 427/1036. This article proposes an English translation of the Risālah together with a brief introduction and discussion.